Brief Report: Maternal Age of Menarche and Adiposity. Issue 3 (May 2016) - Lai, Tsz Chun; Au Yeung, Shiu Lun; Lin, Shi Lin; Leung, Gabriel Matthew; Schooling, C. Mary
Abstract : Background: Earlier age of menarche predicts chronic diseases. Earlier maternal age of menarche is also associated with higher body mass index (BMI) and height into childhood. Methods: We used generalized estimating equations in Hong Kong's "Children of 1997" birth cohort to examine the adjusted association of maternal age of menarche with BMI and height z score, and whether associations varied by maternal birthplace. Results: Earlier maternal age of menarche was not associated with infant BMI but was associated subsequently with higher BMI in childhood and at puberty. Maternal age of menarche was negatively associated with height in children of Hong Kong-born mothers, but positively associated with infant length for children with mothers born in China ( P value for interaction 0.02). Conclusion: These different patterns suggest drivers of adiposity and linear growth differ, and are more influential in some circumstances. Understanding these drivers may indicate setting-specific interventions to prevent childhood obesity. Abstract : Supplemental Digital Content is available in the text.